Contemporary sample stacking in CE - Malá, Zdena; Slampová, Andrea; Gebauer, Petr; Bocek, Petr (Electrophoresis, 2009)
Sample stacking techniques remain an important tool for enhancement of the selectivity and sensitivity of analyses in contemporary CZE. This contribution reviews new knowledge on this topic published since 2006. It is organized according to the operational principles used, which include concentration adjustment, application of a pH step, MEKC and sweeping, and transient ITP. Techniques combining several of these principles and comparative studies are also included.
Keywords: Body Fluids; Electrophoresis, Capillary; Hydrogen-Ion Concentration; elektroforéza kapilární; Inorganic Chemicals; anorganické látky; Food Analysis; lidé; Sensitivity and Specificity; Electrophoresis, Microchip; elektroforéza mikročipová; tělesné tekutiny; senzitivita a specificita; Electrophoresis; Chromatography, Micellar Electrokinetic Capillary; elektroforéza; hmotnostní spektrometrie; chromatografie micelární elektrokinetická kapilární; analýza potravin; Mass Spectrometry; koncentrace vodíkových iontů; Humans